Bunbum ga dhä-yutagum: to make it right again, to remake. (1st September 2020) - Country, Bawaka; Suchet-Pearson, Sandie; Wright, Sarah; Lloyd, Kate; Tofa, Matalena; Burarrwanga, Laklak; Ganambarr, Ritjilili; Ganambarr-Stubbs, Merrkiyawuy; Ganambarr, Banbapuy; Maymuru, Djawundil
ABSTRACT: We say it becomes dhawaḏatj . This is muddled up; the process is not right. In songspirals and ceremonies, when things become dhawaḏatj everyone says 'errgh' and claps to erase the mistake and start again. Songspirals have been here forever. They are Rom, Law. They continually bring us and everything in our Country into being. They must not be muddled. We are still singing and keening these songspirals. As Bawaka Country, we say 'errgh'. Too much has been muddled up: the violences of ongoing colonialism; the Rom not followed; non-humans treated as if they have no voice. Our intention is bunbum ga dhä-yuṯakum, to make it right again, to remake, to build something through its renewal. We are starting again. We want to refuse the mistake and we hope to contribute to processes that heal. We are a more-than-human, Yolŋu-non-Yolŋu Collective from North East Arnhem Land and south eastern Australia. We consider Yolŋu songspirals and the importance of order and process to continually remaking the world. We also reflect on how our working together is part of the songspirals and how this contributes to bunbum ga dhä-yuṯakum, to making it right again, to resisting that which silences or muddles, and to repairing damaged relations and connections.